Designing a Model for Virtual Training of Information Literacy Skills on the Website of Libraries of Medical Sciences Universities in the Country - Afshan Tajbakhsh; Nadjla Hariri; Mohammad Hassanzadeh (پیاورد سلامت)
Background and Aim: The development of the internet and the digitalization of higher education have facilitated the possibility of online course delivery, enabling instructors and students to interact through virtual education. Virtual learning can enhance access to educational resources and services through communication technologies, regardless of time and location. Accordingly, the objective of this study is to design a virtual education model for teaching information literacy skills on the websites of medical university libraries across the country. Materials and Methods: This research was conducted with a mixed approach (qualitative and quantitative). In the first stage, the meta-combination method and the study of previous researches were used according to the research topic and the components were extracted, and after several checks with experts, the necessary concepts and components for the design of the model were extracted. Then, using the Delphi method, experts’ opinions were applied to the output of the meta-combination stage, and the final questionnaire was designed and made available to the statistical community, and finally, in the fourth stage, modeling and validation and fitting of the model took place. Results: The final model was developed using meta-synthesis and validated by experts, comprising 7 main categories, 14 subcategories, and 102 indicators. The main categories include technical factors, strategic factors, instructor-related components, structural factors, educational factors, content-related factors, and assessment and evaluation factors. From the users’ perspective, the content-related subcategory recorded the lowest value, with a score of 0.518 for users and 0.533 for instructors. Conversely, the assessment and evaluation subcategory achieved the highest scores, with 0.916 from the instructors’ perspective, 0.953 jointly from both users and instructors, and 0.842 for structural factors from the users’ perspective. Conclusion: The results of the research showed that there is a significant relationship between the virtual training of information literacy skills on the website of the libraries of medical sciences universities of the country and the mentioned factors. Therefore, the model obtained in this study can be a basis for designing and compiling a framework for electronic learning of information literacy. Acquiring information literacy skills and fostering an information-literate society is a crucial necessity in the information age, particularly for graduate students whose work and activities are inherently tied to research and problem-solving.